Koji amazake produced by double saccharification contains more isomaltose and modifies the gut microbiota in mice - Murakami, Aito; Saito, Atsushi; Namai, Fu; Fujii, Tadashi; Tochio, Takumi; Toida, Jinichi; Shimosato, Takeshi (Frontiers in Nutrition, 2024)
Koji amazake, which is made from rice and rice koji (a product of Aspergillus oryzae), is a traditional Japanese beverage that has glucose as its main component. It also contains isomaltose, which has been reported to have various functionalities related to gut health. In the present study, we attempted to produce amazake with a higher concentration of isomaltose without using any additives by focusing on the saccharification step of rice koji production as a means of creating new value for amazake. Two types of rice koji that were obtained at different fermentation time points were used, and we changed the saccharification process from the usual one step of saccharification to two steps of saccharification using a different type of rice koji for each step. The amazake made by double saccharification (DSA) contained 20 times more isomaltose than the commercial amazake products. In an in vivo study, oral administration of the DSA modified the cecal microbiota in mice. Moreover, changes were seen in the abundances of several gut microorganisms, such as Anaerotignum lactatifermentans, Muribaculum intestinale, and Parabacteroides merdae. These findings indicate that our novel method may be useful for producing amazake with a high isomaltose content that may have health benefits in humans.